Long-term Survival for Patients Undergoing Volatile Versus IV Anesthesia for Cancer Surgery: A Retrospective Analysis. Issue 6 (December 2016) - Wigmore, Timothy J.; Mohammed, Kabir; Jhanji, Shaman
Abstract : (Abstracted from Anesthesiology, 124:69–79, 2016) Volatile inhalational anesthetic (INHA) gases and total IV anesthesia (TIVA) are 2 main classes of drugs used to maintain general anesthesia. In addition, there are a number of retrospective studies suggesting that the use of regional anesthesia during cancer surgery is beneficial, although the reason is uncertain.